Physician acceptability of oral ivermectin versus permethrin in scabies treatment - Genuino, Rowena F.; Batac, Maria Christina Filomena R.; Mariano, Alena Marie B.; Dofitas, Belen L.; Capule, Francis R.; Garcia Jr., Fernando B.; Ladia, Mary Ann J.; Santos, Malaya P.; Yabes, Ailyn M.; Cagayan, Maria Stephanie Fay S. (International Journal of Public Health Science (IJPHS), 2025)
Oral ivermectin may be a cheaper and more convenient alternative to topical permethrin for classic scabies but its acceptability among physicians in the Philippines is underexplored. This qualitative study aimed to investigate physicians’ experiences and perceptions regarding oral ivermectin, alone or in combination with permethrin, and only permethrin in the treatment of classic scabies. We interviewed 15 purposively sampled Filipino physicians: nine have prescribed only permethrin, one has prescribed either oral ivermectin or permethrin alone, and five have prescribed all three regimens for scabies. Interview data were analyzed and thematically organized using the theoretical framework of acceptability (TFA). Our findings reveal mixed awareness and experience with ivermectin among Filipino physicians: while most were generally confident in permethrin as the standard care, combination therapy was reserved as a last resort. These insights highlight the need for ongoing education, clearer guidelines, and further research to improve the efficacy and accessibility of scabies treatments while addressing physicians' varying perceptions and self-efficacy in alternative treatments.